Land and Discover! A Case Study Investigating the Cultural Context of Plagiarism - Handa, N.; Power, C. (Journal of University Teaching and Learning Practice, 2005)
Despite a growing body of evidence, the common causal factors ofplagiarism among international students are still widely seen to be poorlanguage skills or a lack of academic integrity on the part of the students.This research uses the experiences of a particular cohort of students toexplore these assumptions. It investigates and compares the notion ofacademic integrity and the understanding of plagiarism of both Indianpostgraduate students who are currently studying in Australia and studentscurrently studying at Indian universities. Postgraduate internationalstudents from India have studied in English at an undergraduate level inIndia and have a clear understanding of academic integrity in their owncontext. However their undergraduate experience occurs in a culturallydifferent context to that of the Australian university system and they facethe challenge of learning new academic conventions. This paper arguesthat students coming from different educational cultures require proper andexplicit induction into the principles and philosophy behind many westernacademic conventions as different conventions of scholarship in theAustralian education system can create unique difficulties for them. Toaccuse international students in general of a lack of integrity because theyplagiarise or to blame only their lack of language skills for plagiarisingseems to be arguable. Rather, the impact of transition from a differentuniversity culture without explicit academic skills orientation and instructionneeds to be addressed. The paper also points towards the paradox ofpunishment in western universities where international students have toprove their integrity and innocence regarding the ethical principles of a newand foreign culture.